2020
DOI: 10.1002/adma.202002908
|View full text |Cite
|
Sign up to set email alerts
|

Stable Potassium Metal Anodes with an All‐Aluminum Current Collector through Improved Electrolyte Wetting

Abstract: Cost-efficient electrical energy storage systems (ESSs) are key for clean renewable energy based on solar and wind, as well for emerging smart grid applications. [1,2] It is a large but underexploited market and is rapidly attracting scientific interest. [2,3] Because the cost considerations for stationary ESSs are paramount, sodium-and potassium-based technologies are potentially superior to lithium ion batteries (LIBs), being more abundant in terms of precursors while not directly competing with automotive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
89
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(91 citation statements)
references
References 121 publications
2
89
0
Order By: Relevance
“…Figure 7 A shows the Al 2p spectra of the treated films. Both metallic Al (72.2 eV) and Al 2 O 3 (74.2 eV) are detected at the surface of the control film (Al-air) owing to exposure in air, which matches well the theoretic peak positions ( Liu et al., 2020a ). After being treated with PFN-Br and PDINN solution, the Al (2p) metallic core level (Al 2p3/2) ( Figure 7 A) shifts toward higher binding energy (from 72.2 to 72.4 eV) and the Al 2p1/2 peak almost disappears, suggesting electron transfer from metal atoms to organic molecules by strong chemical reaction.…”
Section: Resultssupporting
confidence: 79%
“…Figure 7 A shows the Al 2p spectra of the treated films. Both metallic Al (72.2 eV) and Al 2 O 3 (74.2 eV) are detected at the surface of the control film (Al-air) owing to exposure in air, which matches well the theoretic peak positions ( Liu et al., 2020a ). After being treated with PFN-Br and PDINN solution, the Al (2p) metallic core level (Al 2p3/2) ( Figure 7 A) shifts toward higher binding energy (from 72.2 to 72.4 eV) and the Al 2p1/2 peak almost disappears, suggesting electron transfer from metal atoms to organic molecules by strong chemical reaction.…”
Section: Resultssupporting
confidence: 79%
“…[14] All the abovementioned limitations can be overcome or reduced if dendrite growth/breakage can be prevented during the deposition/ dissolution process. Many studies have been reported on the construction of dendrite-free metal anodes: a) fabrication of modified electrodes or metal substrate surfaces, [15][16][17][18][19][20][21][22][23][24] b) synthesis of new electrolytes, [25][26][27][28][29] c) use of solid electrolytes, [22,[30][31][32] and d) improvement of the electrode-electrolyte interface. [9,15,33,34] However, these studies have rarely focused on the properties, such as the stability of dendrites during charging and discharging, of dendrites.…”
mentioning
confidence: 99%
“…In addition, various strategies for stabilizing the interface have been proposed, including modification of the electrolyte compositions and design of nanostructured or coated electrodes. [ 86–91 ]…”
Section: Fundamental Understanding Of Electrochemical Processesmentioning
confidence: 99%